2021
DOI: 10.1021/acs.estlett.1c00422
|View full text |Cite
|
Sign up to set email alerts
|

Single-Use Face Masks as a Potential Source of Synthetic Antioxidants to the Environment

Abstract: Single-use face masks are a powerful tool for reducing the spread of COVID-19. The usage of single-use face masks has increased enormously since the start of the COVID-19 pandemic, and pollution from the huge volume of discarded single-use face masks may become an environmental issue. This study focuses on synthetic antioxidants (AOs), including synthetic phenolic antioxidants (SPAs) and organophosphite antioxidants (OPAs), used in single-use three-layer face masks. Both SPAs and OPAs were detected in single-u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(60 citation statements)
references
References 40 publications
1
52
0
4
Order By: Relevance
“…Like plastic, PPE can absorb and concentrate contaminants from the surrounding environment, posing risks of contaminant transfer to animals through different trophic levels ( Dobaradaran et al, 2018 ; Akhbarizadeh et al, 2021 , Akhbarizadeh et al, 2021 ; Takdastan et al, 2021 ; Hajiouni et al, 2022 ). Existing studies have documented that masks and wipes contain a wide range of inorganic and norganic contaminants utilized as UV stabilizers, plasticizers, and flame retardants in plastic production, including antioxidants, organophosphate esters, phthalates (di- and mono) and non-phthalates, bisphenols, and plastic additives ( Liu and Mabury, 2021 ; Sullivan et al, 2021 ; Wang et al, 2021b ; Kutralam-Muniasamy et al, 2022 ). Ardusso et al (2021) and De-la-Torre et al (2022) reported the appearance of metallic nanoparticles, such as Ag and Cu nanoparticles on used face masks.…”
Section: Introductionmentioning
confidence: 99%
“…Like plastic, PPE can absorb and concentrate contaminants from the surrounding environment, posing risks of contaminant transfer to animals through different trophic levels ( Dobaradaran et al, 2018 ; Akhbarizadeh et al, 2021 , Akhbarizadeh et al, 2021 ; Takdastan et al, 2021 ; Hajiouni et al, 2022 ). Existing studies have documented that masks and wipes contain a wide range of inorganic and norganic contaminants utilized as UV stabilizers, plasticizers, and flame retardants in plastic production, including antioxidants, organophosphate esters, phthalates (di- and mono) and non-phthalates, bisphenols, and plastic additives ( Liu and Mabury, 2021 ; Sullivan et al, 2021 ; Wang et al, 2021b ; Kutralam-Muniasamy et al, 2022 ). Ardusso et al (2021) and De-la-Torre et al (2022) reported the appearance of metallic nanoparticles, such as Ag and Cu nanoparticles on used face masks.…”
Section: Introductionmentioning
confidence: 99%
“…De forma adicional, algunos aditivos sintéticos antioxidantes (AO) usados en la fabricación de plásticos pueden retardar aún más las reacciones de degradación de las mascarillas descartadas hacia el ambiente, aumentando su daño potencial. Autores como Liu & Mabury, (2021) & Favela et al, (2021 han encontrado la presencia de antioxidantes fenólicos sintéticos y antioxidantes organofosforados en mascarillas.…”
Section: Situaciones O Entornosunclassified
“…Para hallar la masa mundial de mascarillas residuales se consideró la masa media unitaria obtenida previamente. Los valores de antioxidantes sintéticos aportados al ecosistema usaron además las concentraciones halladas por Liu & Mabury, (2021) en su investigación científica. Para establecer los intervalos de confianza, se consideró un alfa de 0,05.…”
Section: Cuantificación De Los Fenómenos Estudiadosunclassified
See 1 more Smart Citation
“…A variety of anthropogenic additives are used in the manufacture of polymers to improve their qualities. Synthetic phenolic antioxidants (SPAs), a group of such additives, are widely used in polymers to retard oxidative degradation and prolong their life spans. 2,6-Di- tert -butyl-4-methylphenol (BHT) is among the frequently used SPAs and its pollution has attracted attention for decades . As BHT is liable to migrate from substrates to the surrounding environment, 3-(3,5-di- tert -butyl-4-hydroxyphenyl)­propionate antioxidants such as pentaerythritol tetrakis­(3-(3,5-di- tert -butyl-4-hydroxyphenyl)­propionate) (AO1010), which have higher molecular weights than BHT, are preferred to be used in polymers to reduce the migration and subsequent contamination. In recent years, high molecular weight SPAs have been preferred over low-molecular-weight SPAs for use in polymers as the former SPAs are less prone to migrate from polymers and thus their use reduces environmental contamination by SPAs. …”
Section: Introductionmentioning
confidence: 99%